Alternativas para aquecimento de aviários frente à problemática do uso de lenha como fonte de energia - Silva, Veridiane Camargo da (2014)
This paper discusses the environmental problems caused by the use of wood as fuel for heating poultry houses in the Southwest region of the state of Paraná, and the consequent degradation of the remaining forest areas of the Atlantic Forest Biome, region in which it operates. As proposed for the solution of this problem were studied and raised two alternative ways of generating heat energy: the pellets and briquettes produced from the reuse of waste, which can be urban, industrial or agricultural. The methodological procedures for the development of the objectives of this research were composed of systematic reviews related to power generation and the processes of degradation of forest cover; the application of questionnaires to producers and consumers of wood for energy generation, and field research in aviaries located within the municipality of Francisco Beltran New Hope and the Southwest. The results obtained demonstrate the process of using wood as the primary resource for heat generation in the region currently aviaries, while demonstrating the possibility of moving to another state, the diffusion and dissemination of the use of alternative fuels such as ecological wood, pellet and briquette called for.